2003
DOI: 10.1111/1540-5826.00077
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Success in Individuals with Learning Disabilities: A Qualitative Analysis of a 20‐Year Longitudinal Study

Abstract: The research described here is part of a larger longitudinal project tracing the lives of a group of individuals with learning disabilities who attended the Frostig Center more than 20 years ago. The purpose of the larger project has been to identify variables that predict successful outcomes for adults with learning disabilities. This article focuses on the qualitative findings obtained using an ethnographic approach to analyzing in-depth interviews with participants. Six previously identified "success attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
192
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(205 citation statements)
references
References 28 publications
11
192
0
2
Order By: Relevance
“…These findings are in line with a number of other investigations that have documented adults with dyslexia being able to develop ingenious strategies to overcome their difficulties (Everatt, Steffert & Smythe, 1999;Gerber et al, 1992;Goldberg et al, 2003;Hellendoorn & Ruijssenaars, 2000;Logan, 2009;McNulty, 2003;Paananen, 2006). In keeping with other published research on practicing teachers with LDs (Ferri et al, 2001;Riddick, 2003;Vogel et al, 2007;Vogel & Sharoni, 2011), compensatory strategies have been confirmed to be of utmost importance for teachers with LD to be successful in their work.…”
Section: Resources For Professional Identity Negotiationsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in line with a number of other investigations that have documented adults with dyslexia being able to develop ingenious strategies to overcome their difficulties (Everatt, Steffert & Smythe, 1999;Gerber et al, 1992;Goldberg et al, 2003;Hellendoorn & Ruijssenaars, 2000;Logan, 2009;McNulty, 2003;Paananen, 2006). In keeping with other published research on practicing teachers with LDs (Ferri et al, 2001;Riddick, 2003;Vogel et al, 2007;Vogel & Sharoni, 2011), compensatory strategies have been confirmed to be of utmost importance for teachers with LD to be successful in their work.…”
Section: Resources For Professional Identity Negotiationsupporting
confidence: 90%
“…Attributes contributing to the employment success in adults with dyslexia consist of external factors as well as a number of internal resources (see Gerber, Ginsberg & Reiff, 1992;Goldberg, Higgins, Raskind & Herman, 2003), of which self-efficacy has been found to be a significant contributor for personal success (Leather et al, 2011). Adults with dyslexia obtaining high self-efficacy beliefs feel competent and satisfied with their job (Leather et al, 2011).…”
Section: Diversity Within the Teaching Workforcementioning
confidence: 99%
“…For example, the study by Sands, Spencer, Gliner, and Swaim (1999), which only identified in-school student success indicators, was excluded because the in-school behaviors were not associated with post-high school employment or further education. Behaviors identified by Goldberg, Higgins, Raskind, and Herman (2003) were included because the qualitative study identified specific attributes that provided a richer definition of constructs identified by quantitative studies, such as "the ability to compartmentalize their disability" (p. 226).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Students must actively seek situations to use their strengths in school and in the community (Gerber et al, 1992;Goldberg et al, 2003;McNulty, 2003). For example, if a student has a disability in the area of written expression, he or she may choose to become a club photographer rather than the club secretary.…”
Section: Actions Related To Strengths and Limitationsmentioning
confidence: 99%
“…Martin, Hennessey, McConnell, and Kazimi (2011) view selfdetermination as a concept built upon 8 constructs: knowledge of strengths and limitations, disability awareness, employment, goal setting and attainment, persistence, proactive involvement, self-advocacy, and utilization of supports. Motivation, drive and tenacity are considered key to achieving one's life goals (Berry & Domene, 2015;Boldt, 1999;Burbank, 2015;Goldberg, Higgins, Raskind, & Herman, 2003;. We must also be mindful that many people with disabilities need us to help them find their voices in expressing the very things that they want in their lives; for without such support they can often be directed towards options for living and working that are far from ideal (Migliore, Mank, Grossi, & Rogan, 2007).…”
Section: Positive Personal Attributesmentioning
confidence: 99%